El Cajón al muerto en Matanzas: configuración ritual festiva del complejo religioso Ocha-Ifá - Balbuena Gutiérrez, Bárbara (Comparative Cultural Studies: European and Latin American Perspectives, 2020)
The dead drawer is one of the festive ritual configurations that is often made, as part of the new traditions incorporated into Ocha’s religious practices. This is a key example to demonstrate the processes of cultural hybridization to which the cult has been subjected and where both religious components of the Espiritismo and the Regla de Palo in Cuba, as well as representative secular expressions of the cultural heritage of the nation, such is the case of the Rumba. The fundamental objective of the study is to assess the importance that this holiday has taken on as a way of paying tribute to the dead or eggun and in fulfillment of the maxim “Ikú logbi Ocha” (the dead gave birth to the saint). It is built an analysis of this celebration dedicated to the undivinized ancestors of the Regla de Ocha, taking into account the origin, its motivations, the ritual configuration and the musical-dance expressions involved. The symbolic meaning of each of the actions performed in this festive ceremony is also considered.